Channels of Desire : Mass Images and the Shaping of American Consciousness. - Ewen, Stuart (University of Minnesota Press, 1992)
Stuart Ewen and Elizabeth Ewen offer a telling examination of the rise of mass-produced imagery in the United States, tracing the pivotal role that such images played in the genesis and development of the American imagination. Beginning with the rise of the machine and the emergence of consumerism as a common way of life, the authors lay a strong foundation for an understanding of the twentieth-century American media culture. Spanning a wide range of fascinating subjects-movies, fashion, tabloid journalism-Ewen and Ewen offer forceful insights into the mechanisms that link alluring images and.